An Endemic Plant of the Mediterranean Area: Phytochemical Characterization of Strawberry Tree (Arbutus unedo L.) Fruits Extracts at Different Ripening Stages - Scarano, Pierpaolo; Guida, Rosa; Zuzolo, Daniela; Tartaglia, Maria; Prigioniero, Antonello; Postiglione, Alessia; Pinto, Gabriella; Illiano, Anna; Amoresano, Angela; Schicchi, Rosario; Geraci, Anna; Sciarrillo, Rosaria; et al. (Frontiers in Nutrition, 2022)
This work focused on the extraction, quantification, and characterization of bioactive compounds of Arbutus unedo L. fruits, comparing the results obtained from the different ripening states. Extractions were performed by different methods (such as maceration extraction and ultrasonic extraction) and food grade solvents (aqueous and hydroalcoholic solvents) in each of the all ripening states (four states considered, associated with four different colors, i.e., green, yellow, orange, and red). The presence of (poly)phenols was quantified and characterized, and scavenging activity was determined by the Folin–Ciocâlteu reagent and the DPPH method, respectively. The content of bioactive compounds was characterized by LC-MS/MS, such as multiple reaction monitoring (MRM) mass spectrometry. The results showed that ultrasound-assisted extraction (UAE) performed better than maceration extraction; ethanol–water mixture extracts showed a more positive effect than the use of aqueous extracts regarding the content of total phenolic compounds. Overall, the total phenolic compounds in the EtOH:H2O mixture at a ratio of 7:3 (v:v) were higher than that of the other solvents for both extraction methods. Some bioactive molecules were characterized for the first time in the extracts of A. unedo. The chemical profile of the strawberry tree extracts depended on the degree of fruit ripeness. The results suggest that A. unedo fruits may be of great interest for food and nutraceutical applications.